Future and Career Anxiety: The Contribution of Career Planning in Minimizing Quarter-Life Crisis on Final-Year Students - Alfiesyahrianta Habibie; Nur Aisyah Rahmani Nasution; Rika Aulia Sari; Farah Diba Maharani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Quarter-life crisis is increasingly being discussed as a phase of uncertainty among young adults, one of the triggers of which is a lack of career planning, causing individuals to feel unprepared to face life after higher education. This study aimed to examine the role of career planning in quarter-life crises among students. The research method was a quantitative survey of 153 respondents, with the criterion being students aged 18–29 years who were studying or came from East Kalimantan. Data were collected using the Developmental Crisis Questionnaire (DCQ-12) scale by Petrov et al. (2021) and Career Planning by Wang et al. (2022) for students. Data analysis was conducted using simple linear regression through the JASP. The results showed that career planning influenced the level of quarter-life crisis among students with a significant value (p<0.001) and a contribution of 46%. This means that the higher the level of career planning, the lower the level of quarter-life crisis among students. These findings emphasize the importance of career planning for final-year students facing uncertainty of the future after graduation and managing stress in a more adaptive manner.